Transformation of Rumah Gadang Into Homestasy in Traditional Village of Nagari Sijunjung - Ermayanti, Ermayanti; Indrizal, Edi; Irwandi, Ade (Lasigo Akademia Indonesia, 2023)
This research explains the transformation of Rumah Gadang in the Traditional Village of Nagari Sijunjung. Rumah Gadang is an embodiment of Minangkabau culture both in place and space and is one of the characteristics of an ideal sociocultural life. But over time, Rumah Gadang has changed its function to become an inn on the tourism agenda. This certainly raises the question of what is the definition of Rumah Gadang for Minangkabau people today. Through observation methods, in-depth interviews and utilizing previous writings, the phenomenon of Rumah Gadang in the Traditional Village of Nagari Sijunjung which is used as an inn and tourist destination through the concept of rural tourism is examined. The results show that Rumah Gadang is not only a place, but functions as a space in carrying out social, economic and cultural life. The transformation of Rumah Gadang to lodging causes some social and cultural functions to be limited but economic functions increase. These two sides of the coin are the intertwining that is happening in the Traditional Village of Nagari Sijunjung where culture and tourism are packaged together. In the end, economic factors through the tourism industry make the survival of Rumah Gadang for Sijunjung people.